2021
DOI: 10.1097/j.pain.0000000000002429
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is associated with characteristic features of the dysfunctional chronic pain phenotype

Abstract: The dysfunctional chronic pain (Dysfunctional CP) phenotype is an empirically identifiable CP subtype with unclear pathophysiological mechanisms that cuts across specific medical CP diagnoses. This study tested whether the multidimensional pain and psychosocial features that characterize the dysfunctional CP phenotype are associated broadly with elevated oxidative stress (OS). Measures of pain intensity, bodily extent of pain, catastrophizing cognitions, depression, anxiety, sleep disturbance, pain interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Increasing evidence suggest isoprostanes are involved in the complex interplay underlying cardiovascular homeostasis between low-grade in ammation, lipid peroxidation, and platelet activation [48]. To date there are few clinical studies aimed at evaluating isoprostanes or other arachidonic acid derivatives in chronic pain [49] and speci cally in migraine [50]. Helmersson and colleagues found no differences in isoprostane urine rates between ictal and interictal periods in 21 patients with migraine [51].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggest isoprostanes are involved in the complex interplay underlying cardiovascular homeostasis between low-grade in ammation, lipid peroxidation, and platelet activation [48]. To date there are few clinical studies aimed at evaluating isoprostanes or other arachidonic acid derivatives in chronic pain [49] and speci cally in migraine [50]. Helmersson and colleagues found no differences in isoprostane urine rates between ictal and interictal periods in 21 patients with migraine [51].…”
Section: Discussionmentioning
confidence: 99%
“…Results regarding associations between preoperative OS and preoperative pain and psychosocial status in this project have been reported separately. 9…”
Section: Designmentioning
confidence: 99%
“…3,6,8,16,24,38 Consistent with associations between OS and pain, our recent findings in patients with osteoarthritis preparing to undergo TKA indicated that elevated preoperative OS was associated with higher preoperative pain intensity, functional limitations, depression, and catastrophizing, as well as more widespread chronic pain. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated oxidative stress is associated with OA pain. A measurement of 84 patients with chronic osteoarthritis show that higher oxidative stress is associated with greater pain intensity, more widespread pain, greater pain catastrophizing, higher pain interference, and lower function [13]. Mitochondria are the predominant source of intracellular reactive oxygen species (ROS) which is generated by the reaction between oxygen and a little quantity of electrons form electron transport chain (ETC) [14,15].…”
Section: Introductionmentioning
confidence: 99%